2008
DOI: 10.1088/0022-3727/41/9/095102
|View full text |Cite
|
Sign up to set email alerts
|

Er3+and Yb3+concentration effect in the spectroscopic properties and energy transfer in Yb3+/Er3+codoped tellurite glasses

Abstract: Spectroscopic properties of Yb3+/Er3+ codoped tellurite glasses as a function of Er3+ and Yb3+ concentration have been investigated. Under 970 nm excitation three strong up-conversion emission bands centred at 525, 546 and 656 nm were observed, and the characteristic near infrared emission band was centred at 1.53 µm. With fluorescence and radiative lifetime the quantum efficiency (QE) of infrared (1.53 µm) and visible upconversion (546 and 660 nm) emissions was calculated. The maximum stimulated emission cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 31 publications
0
16
1
1
Order By: Relevance
“…In the ET process, decay time depends on the intermediate state of decay, which for Yb is much larger than 4 I 11/2 of Er [36]. In addition, it has been shown that the presence of Yb avoids clustering of the Er ion, enhancing all spectroscopic properties [37]. Yb-Er-codoped nanocrystals also present an increment on the effective decay time with the use of surfactant.…”
Section: Fluorescence Decay Timementioning
confidence: 99%
“…In the ET process, decay time depends on the intermediate state of decay, which for Yb is much larger than 4 I 11/2 of Er [36]. In addition, it has been shown that the presence of Yb avoids clustering of the Er ion, enhancing all spectroscopic properties [37]. Yb-Er-codoped nanocrystals also present an increment on the effective decay time with the use of surfactant.…”
Section: Fluorescence Decay Timementioning
confidence: 99%
“…Fig. 3 exhibits the energy level diagram of Er 3+ and Yb 3+ in NMAG glasses [42][43][44][45][46][47]. Under low-power excitation of 974 nm laser, for 4 F 9/2 → 4 I 15/2 transition, Er 3+ ions are excited to the 4 I 11/2 level by the ground state absorption (GSA) and the energy transfer (ET) from Yb 3+ , and then partly relax nonradiatively to the 4 I 13/2 level.…”
Section: Green and Red Up-conversion Emissions Of Er 3+mentioning
confidence: 99%
“…This feature has the effect of both increasing the efficiency of the Yb 3+ to Er 3+ energy transfer and reducing the concentration quenching of the Er 3+ ions [11,12]. Moreover, the codoping of Yb 3+ ions with Er 3+ ions in different glasses has yielded enhanced luminescence properties of the Er 3+ ions [13]. So, an important need for rigorous investigation of the codoped Er 3+ Yb 3+ ions in various glass matrices exists, with a view to achieving unprecedented results in telecommunication technology [10,14,15].…”
Section: Introductionmentioning
confidence: 99%